Gross Domestic Product and Household Consumption Affect Gross Savings: A Long-Term Time Series Analysis in Indonesia - Hasibuan, Rizki Khairani; Septiawati, Melliani; Bellia, Aulia Biea; Cahyani, Amelia Putri Indah; Maharani, Astriani Puspita; Nuraya, Ahmad Setiawan (Indonesia Banking School, 2025)
This study aims to analyze the effect of national income, interest rates, and household consumption on the savings in Indonesia. The data used is secondary annual time series data for the period 2004-2023, obtained from the Central Bureau of Statistics and Bank Indonesia. The analysis method used is multiple linear regression with the Ordinary Least Squares (OLS) approach. The results showed that simultaneously the three independent variables had a significant effect on savings. Partially, national income has a positive and significant effect, household consumption has a negative and significant effect, while interest rates have a positive but insignificant effect on the level of savings. These results suggest the importance of macroeconomic strategies that support income growth and consumption efficiency to strengthen the saving capacity of Indonesians.